Activities of Serum Adenosine Deaminase and its Isoenzymes in Patients with Systemic Lupus Erythematosus, Rheumatoid Arthritis, Ankylosing Spondylitis and Myasthenia Gravis - Zhao-wei, Gao; Zhao, Guan-hua; Li, Rui-cheng; Wang, Hui-ping; Liu, Chong; Zhang, Hui-zhong; Dong, Ke (Aktuelle Rheumatologie, 2019)
Objective The aim of this study was to evaluate the changes and diagnostic value of serum ADA activity in autoimmune diseases, including systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), ankylosing spondylitis (AS), and myasthenia gravis (MG).Methods Serum ADA activity, including total ADA (tADA) and its isoenzymes (ADA1 and ADA2), was determined in patients with different autoimmune diseases (144 RA, 114 SLE, 55 AS, 68 MG). The changes in serum ADA activity in patients were analysed. A receiver operating characteristic (ROC) curve analysis was applied to evaluate the diagnostic performance of serum ADA activity.Results Compared with healthy controls, the serum tADA activity in SLE patients was significantly increased (p<0.001), while the serum tADA activity in patients with RA, AS and MG did not change (p>0.05). The ROC analysis showed that the optimal cut-off value of serum tADA activity for SLE diagnosis was 10.5 U/L (79.8% specificity and 74.6% sensitivity; likelihood ratio (LR): 3.693; p<0.001). Moreover, our results showed that there were no significant changes of ADA1 and ADA2 activity in RA, AS and MG patients, while the serum ADA2 activity was significantly increased in SLE patients. The ROC analysis showed that ADA2 activity could be used in diagnosing SLE with 75.4% specificity and 78.1% sensitivity (LR: 3.175). Based on the ROC curve analysis, serum tADA activity (79.8% specificity and 74.6% sensitivity; likelihood ratio (LR): 3.693) and ADA2 activity (75.4% specificity and 78.1% sensitivity; LR: 3.175) are unlikely to be used in diagnosing SLE. Furthermore, there was a positive correlation between tADA activity and SLE disease activity (r=0.303, p=0.010). Notably, serum tADA activity in SLE patients with arthritis was higher than in patients without arthritis (p=0.005), which suggests that tADA activity might be related to lupus arthritis.Conclusion These findings suggest that serum tADA and ADA2 activity might play an important role in SLE progression.
Keywords: ADA-Aktivität; Isoenzym; Autoimmunerkrankung; Diagnose